Kelayakan Bahan Ajar Berbantuan Media Flipbook Pada Materi Stoikiometri Kimia SMA Fase F - Tengker, Soenandar M. T.; Tiwa, Reiva E.; Lumingkewas, Sonny (General Chemistry Journal, 2025)
This research aims to test the feasibility of media-assisted Stoichiometry teaching materials flipbook for SMA Phase F. This research consists of three stages, namely creating, validating and improving media-assisted teaching materials flipbook. Validation uses a research instrument in the form of an assessment questionnaire which includes format, content, language, practicality and effectiveness, consisting of 14 criteria. Validation of media-assisted teaching materials flipbook carried out by three validators consisting of lecturers in the Chemistry Department, FMIPAK, Manado State University. The research results show an average total validation (RTV) of 3.38 this teaching material is classified as valid